Determination of carotene, tocopherols and tocotrienols in residue oil from palm pressed fiber using pressurized liquid extraction-normal phase liquid chromatography - Sanagi, M. Marsin (Elsevier B.V., 2005)
Pressurized liquid extraction (PLE) along with normal phase liquid chromatography (NPLC) is evaluated as a new approach for the determination of -carotene and Vitamin E isomers in residue oil obtained from palm pressed fiber (PPF). The relative extraction recoveries obtained by optimized PLE were found to be equivalent (~100%) to conventional Soxhlet extraction. Optimized PLE was obtained (5 g of sample, 80 ◦C, 1500 psi, 2× 10 min static extractions with flush volume 50%) combined with NPLC system. Typical extractions give 3.7–4.0 mg ml-1 of Vitamin E isomers and -carotene of 3.3–3.5 mg ml-1, which is similar to or greater than classical Soxhlet extraction with n-hexane or chloroform. The new developed method demonstrated an acceptable performance with good efficiency in terms of total extraction time, total solvent usage, total -carotene and Vitamin E isomers contents as well as exceptional method repeatability. © 2005 Published by Elsevier B.V.